2011
DOI: 10.1371/journal.pntd.0001407
|View full text |Cite
|
Sign up to set email alerts
|

Combining Climatic Projections and Dispersal Ability: A Method for Estimating the Responses of Sandfly Vector Species to Climate Change

Abstract: BackgroundIn the Old World, sandfly species of the genus Phlebotomus are known vectors of Leishmania, Bartonella and several viruses. Recent sandfly catches and autochthonous cases of leishmaniasis hint on spreading tendencies of the vectors towards Central Europe. However, studies addressing potential future distribution of sandflies in the light of a changing European climate are missing.MethodologyHere, we modelled bioclimatic envelopes using MaxEnt for five species with proven or assumed vector competence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 91 publications
(111 reference statements)
2
63
1
5
Order By: Relevance
“…Our model finds, in contrast the results of Fischer et al (2011a), that the Benelux States may not be suitable for Phlebotomus species, because they don't favor the short, relatively cold and rainy summers (Kennewick et al, 2010). Fischer et al (2011a) expected no migration from southeastern direction, which is strengthened by our results. We found that to the end of the 2060's the expansion of P. ariasi and P. perniciosus to Central Europe is most likely among the studied species.…”
Section: Comparison Of Our Results To the Literaturecontrasting
confidence: 83%
“…Our model finds, in contrast the results of Fischer et al (2011a), that the Benelux States may not be suitable for Phlebotomus species, because they don't favor the short, relatively cold and rainy summers (Kennewick et al, 2010). Fischer et al (2011a) expected no migration from southeastern direction, which is strengthened by our results. We found that to the end of the 2060's the expansion of P. ariasi and P. perniciosus to Central Europe is most likely among the studied species.…”
Section: Comparison Of Our Results To the Literaturecontrasting
confidence: 83%
“…Using the example of sandflies, it has been demonstrated that the dispersal of disease vectors on the continental scale can be evaluated by creating artificial cost surfaces that include several landscape features that are attributed with cost factors [44]. Consequently, the pathway with least costs for a species' dispersal can be considered as the most likely path of the species to move across landscapes.…”
Section: Continental Dispersal Pathwaysmentioning
confidence: 99%
“…Originating in southeast Asia, Aedes albopictus is spreading globally and was reported in Albania in 1979 [97]. The mosquito is now established in southern parts of Europe [98,99] and can transmit not only Chikunguya, but also, among others, Dengue fever [100][101][102][103].…”
Section: Climate-sensitive Infectious Diseasesmentioning
confidence: 99%
“…Observed and Projected Effects (6) Malaria in Portugal [89] Malaria in Germany [92] Malaria in Turkey [90] Aedes albopictus in Europe [98] Malaria in Spain [91] Recent and future Aedes albopictus suitability [99] WNF in Israel [93] Dengue in Europe [100] WNF in Hungary and Austria [94] Dengue in Europe [103] Chikungunya in Italy [96] Dengue and Chikungunya in Europe [101] Dengue in Madeira 2012 [102] Ticks transmit climate-sensitive infectious diseases including Crimean Congo hemorrhagic fever [108,109], Lyme borreliosis [110][111][112], tick-borne encephalitis [113][114][115][116][117][118][119][120] and Tularemia [121]. Several studies identified in the literature review do not report on climate change and tick-transmitted diseases, but instead describe changes in tick distribution, specifically in the United Kingdom [122], Slovenia [123], and the Czech Republic [124].…”
Section: Observed Effect (7)mentioning
confidence: 99%